Local Governments' Policies of Investments in Environmental Protection - Beke-Trivunac, Jozefina J.; Jovanović, Larisa (Industrija, 2013)
The present paper tries to investigate the impact of the decrease of local governments' budgets on the local government environmental investment policies. The significant adverse variances between budgeted and actual amounts point to the fact that environmental protection is not yet a high priority issue in the local government management policies. The analysis of the structure of planned and actual investments by purpose, and their realization index show that local governments allocate the largest amount of expenditures in waste management. Moreover, a high index of realization of these expenditures additionally indicates that waste management has the highest priority within the environmental function in both years, what could be explained by regulated and stable financing of this function by earmarked funds. The results are instructive for local governments and may encourage them to increase the share of earmarked funds for financing environmental protection. The analysis of environmental protection investment policies of local governments in this paper is based on comparison of the series of indices calculated as the relation between actual and budgeted amounts of total, environmental and components of environmental expenditures, as well as of total and environmental income of local governments.
Keywords: Local government; Investment; Government; Expenditure; Environmental protection; Environmental expenditure; Earmarked funds; Serbia